Socio-economic determinants of media attendance for forest conservation support information in protected areas of Southwestern Nigeria (2004)
The study investigated the impact of some socio-economic characteristics (sex, marital status, family size, occupation, farm size, education, nativity, and duration of resident) of the residents of some protected areas (Oluwa and Shahsa forest reserves and Old Oyo National Park enclaves) in Southwestern Nigeria on media attendance for forest conservation support information (FCSI). The media investigated were forestry personnel, agricultural extension workers (AEWs), village/religious meetings, radio, television, newspaper/magazine, pamphlets, billboard, town criers and festival gatherings. Purposive and multi stage random sampling techniques were used to choose respondents from the target population for the study: residents of communities within and around the protected areas. Two hundred set of questionnaires were administered on the randomly selected local residents of the protected areas. Data generated were analyzed using inferential and descriptive test statistics. The study revealed that radio is the most appropriate medium (39%) for sourcing FCSI in the study area. This was followed by the use of community/religious leaders’ forum (29.1%) and AEWs (15.8%). It also revealed that there were no relationship between the socio-economic characteristics of the residents and their attendance to forestry personnel (F=1.36; P.r > 021), television (F=0.28; Pr. > 0.97), newspaper/magazine (F= 1.96; Pr.> 0.05), pamphlets (F= 0.43; Pr. > 0.91) and festival gatherings (F= 1.69; Pr. > 0.10). However, some of the socio-economic characteristics of residents impact their attendance to AEWs (F= 35.02; Pr. < 0.00), village/religious meetings (F= 4.97; Pr. < 0.03), radio (F= 10.75; Pr. < 0.001), folklore, songs and drama (F= 2.82; Pr. < 0.02) and town crier media for FCSI. It was also observed that occupation of residents has the highest, while acquisition of western education has the least impact on media attendance for FCSI. Education only influences attendance to radio (t= 2.74; Pr. < 0.005). It was therefore suggested among others, that effort should be made to improve environmental education and extension services in the study area.